Comparative proteomic analysis provides new insights into ear leaf senescence of summer maize (Zea mays L.) under field condition - Shan-shan WEI; Xiang-yu WANG; Peng LIU; Ji-wang ZHANG; Bin ZHAO; Shu-ting DONG (Journal of Integrative Agriculture, 2016)
As the most important organ in plant photosynthesis, the leaf plays an important role in plant growth and development. Leaf senescence is associated with fundamental changes in the proteome. To research the molecular mechanisms of leaf senescence, protein expression in senescing maize ear leaves grown under field conditions was analyzed using two-dimensional gel electrophoresis and matrix-assisted laser desorption/ionisation time-of-flight/time-of-flight mass spectrometry (MALDI-TOF/TOF MS). A total of 60 senescence-associated proteins were identified. The identified proteins are involved in many biological processes, especially energy, metabolism and protein synthesis. Several of the identified proteins have not been previously reported as senescence-associated, including glycine-rich RNA-binding protein.